Yanna Hadatty, Norma Lojero Vega y Rafael Mondragón (coords.), La revolución intelectual de la Revolución mexicana (1900-1940). Universidad Nacional Autónoma de México, México, 2019; xxxvi + 534 pp. - Rodríguez González, Yliana (El Colegio de México, 2020)
Resumen